Evaluation of Root Coverage Using Subepithelial Connective Tissue Graft in Combination with Tunnel Technique - Zaman, Jawairia; Azeem, Muhammad; Kaleem, Hafiza Mahnoor; Mirza, Armaghan Israr; Ashraf, Zukhruf; Toosy, Waleed Javaid (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the frequency of complete root coverage when using a graft of subepithelial connective tissue inserted with tunneling technique in patients with gingival recession.Study Design: Prospective longitudinal study.Place and Duration of Study: Department of Oral and Maxillofacial Surgery, de’Montmorency College of Dentistry, Punjab Dental Hospital, Lahore, Pakistan, from Apr to Oct 2022.Methodology: A total of 80 cases, male and female, diagnosed with gingival recession classified as Millers Classes I or II, between the ages of 18 to 65 years, were enrolled in this study. Patients who smoked, had pre-existing medical comorbidities, exhibited parafunctional habits (bruxism, nail biting, clenching) or had preexisting periodontal disease were excluded. Probing depth at the site of gingival recession was assessed on the 1st, 7th, 21st and 90th day post-operatively. The success of the procedure was determined by the presence or absence of complete root coverage after 90 days.Results: Mean age was found to be 35.16±9.47 years, with 15(18.8%) male patients and 65(81.3%) female patients. Complete root coverage was present in 57(71.3%) patients. The mean preoperative periodontal depth was 1.17±0.28 mm which improved to mean 1.03±0.25 mm at 90th post-op day, this was found to be statistically significant.Conclusion: Root coverage with subepithelial connective tissue graft using tunnel technique showed comparable results to already existing techniques.